PERANCANGAN CO-WORKING SPACE DENGAN PENDEKATAN BIOPHILIC DESIGN - Lily, Selda Mishelie; Susan, M.Y; Istanto, Freddy Handoko (Universitas Ciputra Surabaya, 2020)
The increasing of Urbanization especially in urban area cause interaction between human and nature decreased, most of the time is spent in indoor especially office area. This phenomena has caused decreased of human well-being in physical and psychological. Decreased interaction between human and nature called Nature Deficit Disorder. Therefore is it suggested that office area using Biophilic Design approach. Biophilic Design can give positive aspects like increase productivity, reduce stress, mood booster, and many more. Intano | Co-work is a business that operates in the field of co-working space which is included in the category of offices. Intano | Co-work wants a co-working space that is comfortable and can attract visitors. So that by implementing biophilic design in the building of co-working space it can provide added value to the co-working space because biophilic design can provide positive effects including reducing stress, increasing concentration, and productivity for tenants and workers. Elements of biophilic design are applied using the guidelines of 14 elements of biophilic design compiled by Terrapin Bright Green. Biophilic design is applied through spatial planning, material use, lighting systems, and air conditioning systems. In this building, it has many openings as access to green areas. The building maximizes natural lighting and airing. Maximizing natural lighting is applied through the use of skylights while natural exposure by maximizing cross-ventilation. Keywords: Biophilic Design, Business Plan, Co-working space, Interior Architecture